Electronic Properties of Atomic Layer Deposited HfO2 Thin Films on InGaAs Compared to HfO2/GaAs Semiconductors - Irving K. Cashwell; Donovan A. Thomas; Jonathan R. Skuza; Aswini K. Pradhan (Crystals)
This paper demonstrates how the treatment of III-V semiconductor surface affects the number of defects and ensures the conformal growth of the high-k dielectric thin film. We present the electrical properties of an HfO2/InGaAs-based MOS capacitor, in which growth temperatures and surface treatments of the substrate are two key factors that contribute to the uniformity and composition of the HfO2 thin films. A remarkable asymmetry observed in capacitance versus voltage measurements was linked to the interface defects and charge redistribution, as confirmed from X-ray photoelectron spectroscopy. The GaAs substrates that were etched with only NH4OH showed a large frequency dispersion and a higher surface roughness; however, the HfO2 thin films grown on GaAs pre-treated with both NH4OH etching and (NH4)2S passivation steps produced a desirable surface and superior electronic properties.